THE MAIN DIRECTIONS OF THE DEFINITION OF REGIONAL DEVELOPMENT BENEFITS (FOR EXAMPLE, NIZHEGORODSKIY REGION) - E. Frantseva-Kostenko (Вестник университета)
Currently in a systemic crisis and the availability of sanctions in the first place is the problem of development of regions of Russia, therefore, the definition of the main socio-economic trends of development of regions is the most relevant. Research and analysis of fields of activity of separate regions enables determination of the trajectories of regional development in the whole country. The article identifies the main positive and negative trends in socio-economic development of Nizhniy Novgorod region, classified according to three main spheres of life: social, economic and information based on which the basic problems of territorial development, which are the causes of instability in the region.